Butterflies' biodiversity of Souk Ahras Forest (Mechroha and Ouled Driss North east of Algeria) - Hamza Saouli, Abdelhak Boucif, Ryma Djabourabi, Hana soualah Alila (African Journal of Ecology, 2022)
This study investigated for the first time species richness, abundance of butterflies and disturbed habitats in Souk Ahras Forest. The assessment of butterflies' diversity and relative abundance was conducted from July 2019 to July 2021. We recorded 60,696 individuals of 49 butterfly species belonging to six families (Papilionidae, Pieridae, Lycaenidae, Nymphalidae, Hesperiidae and Sphingidae). Nymphalidae was dominant by 19 species, followed by Lycaenidae 13 species, Pieridae 10 species, Hesperiidae 4 species, Papilionidae 2 species and diurnal moths ‘Sphingidae’ with only one species. The highest number of species was recorded in oaks groves (medium high altitude) with 35 species; in terms of abundance, grassland (low altitude) dominates in number ( n = 20,094). The lowest species diversity (S = 7) and number of individuals ( n = 1227) were recorded in the Dense tree stratum scrub station which records significant water pollution. We notice that the abundance of butterflies was important during the spring and summer periods but less important during the winter. Landscape composition and habitat influence butterfly diversity and their dynamics. Many species used more than one distinct habitat type, or just one special habitat; we suggest that vegetation cover is an important mechanism for butterfly diversity persistence in forest ecosystems mosaics.